Genomic Relatedness of Chlamydia Isolates Determined by Amplified Fragment Length Polymorphism Analysis - Meijer, Adam (American Society for Microbiology, 1999)
The genomic relatedness of 19 Chlamydia pneumoniae isolates (17 from respiratory origin and 2 from atherosclerotic origin), 21 Chlamydia trachomatis isolates (all serovars from the human biovar, an isolate from the mouse biovar, and a porcine isolate), 6 Chlamydia psittaci isolates (5 avian isolates and 1 feline isolate), and 1 Chlamydia pecorum isolate was studied by analyzing genomic amplified fragment length polymorphism (AFLP) fingerprints. The AFLP procedure was adapted from a previously developed method for characterization of clinical C. trachomatis isolates. The fingerprints of all C. pneumoniae isolates were nearly identical, clustering together at a Dice similarity of 92.6% (± 1.6% standard deviation). The fingerprints of the C. trachomatis isolates of human, mouse, and swine origin were clearly distinct from each other. The fingerprints of the isolates from the human biovar could be divided into at least 12 different types when the presence or absence of specific bands was taken into account. The C. psittaci fingerprints could be divided into a parakeet, a pigeon, and a feline type. The fingerprint of C. pecorum was clearly distinct from all others. Cluster analysis of selected isolates from all species revealed groups other than those based on sequence data from single genes (in particular, omp1 and rRNA genes) but was in agreement with available DNA-DNA hybridization data. In conclusion, cluster analysis of AFLP fingerprints of representatives of all species provided suggestions for a grouping of chlamydiae based on the analysis of the whole genome. Furthermore, genomic AFLP analysis showed that the genome of C. pneumoniae is highly conserved and that no differences exist between isolates of respiratory and atherosclerotic origins.